Ovarian dysgerminoma with Müllerian anomaly: a case report - Ha Na Kim; Jung Mi Byun; Jin Ok Park; Hye Kyoung Yoon; Da Hyun Kim; Dae Hoon Jeong; Young Nam Kim; Kyung Bok Lee; Moon Su Sung (Korean Society of Obstetrics and Gynecology, 2020)
Müllerian anomalies are rare deformities in women, and only a few cases concerning gynecologic malignancies arising in patients with congenital uterine malformations have been reported. Herein, we present the case of a 34-year-old woman with dysgerminoma with a Müllerian anomaly (uterus didelphys). She had secondary amenorrhea, and an ovarian mass and uterus didelphys were discovered during examination. After right salpingo-oophorectomy, the tumor was confirmed as dysgerminoma, and a chromosome study revealed a normal female karyotype (46, XX). The patient completely responded to 6 cycles of chemotherapy. To our knowledge, this is the first reported case of dysgerminoma with uterus didelphys. Although gynecologic malignancies in patients with Müllerian anomalies are very rare, clinicians should be aware of the coexistence of gynecologic malignancies and uterine malformations.